Perilaku pencarian informasi miner cryptocurrency di grup Facebook Miner Indonesia - Syahid, Fakhrie Nuryana; Damayani, Ninis Agustini; Rizal, Edwin (Jurnal Informatio, 2024)
This study examines the information-seeking behavior related to mining and cryptocurrency exhibited by cryptocurrency miners in the Facebook group Miner Indonesia. The research aims to investigate the information-seeking behavior concerning mining and cryptocurrency among cryptocurrency miners within the Facebook group Miner Indonesia. The study employs a qualitative method with a case study approach. Data collection techniques include observation, interviews, and literature review. The research model utilizes David Ellis's model, which comprises six stages: starting, chaining, browsing, differentiating, monitoring, and extracting. Four members of the Facebook group Miner Indonesia serve as informants for this study. The results indicate that during the starting phase, informants begin to comprehend the information they require regarding mining and cryptocurrency. In the chaining phase, informants conduct more in-depth searches to fulfill their remaining information needs. During the browsing stage, informants utilize internet resources such as Google, YouTube, Facebook, and Reddit to seek necessary information. In the differentiating phase, informants compare information obtained from Facebook with other information sources. The monitoring stage involves informants regularly observing group posts. In the extracting phase, informants apply the acquired information by implementing it on their mining equipment. In conclusion, the researcher found that all four informants engaged in the six stages of information-seeking behavior before obtaining the required information.